Improving Students' Vocabulary through the Use of Pictionary Game - Alya Noor Khalishah; Rofiqoh; Andi Patmasari; Mukrim (Institut Agama Islam Negeri Palopo, 2024)
This research is aimed at proving if the use of pictionary game can improve vocabulary of the eighth-grade students of SMP Negeri 5 Sigi. This research used a quasi-experimental design consisting of experimental and control groups. The Population of this research was the eighth-grade students of SMP Negeri 5 Sigi. This research used a purposive sampling technique to select the sample. The sample of this research was two classes, in the amount 56 students of VIIIA and VIIIB. During the data collection process, this research used a vocabulary test. The test was administered twice as pre-test and post-test. The vocabulary test as the data was analyzed statistically. The findings shows that the mean score of the experimental group improved from pre-test to post-test, i.e. from 45.58 to 74.40, while the mean score of control groups improved from 45.11 to 68.21. The data were statistically analyzed using the t-counted formula with degrees of freedom (df) = Nx + Ny - 2 = 28 +28 - 2 = 54. The analysis results show that the t-counted value is 2.358 while the t-table value is 1.674. It means that the t-counted is higher than the t-table. It can be interpreted that the hypothesis was accepted. Therefore, pictionary game can improve vocabulary of the eighth-grade students of SMP Negeri 5 Sigi. The implication of this finding to the teaching practice is that teachers need to apply the pictionary game to make teaching a vocabulary better